Understanding the U.S. illicit tobacco market: characteristics, policy context, and lessons from international experiences - Reuter, Peter (The National Academies Press, 2015)
"Tobacco use has declined because of measures such as high taxes on tobacco products and bans on advertising, but worldwide there are still more than one billion people who regularly use tobacco, including many who purchase products illicitly. By contrast to many other commodities, taxes comprise a substantial portion of the retail price of cigarettes in the United States and most other nations. Large tax differentials between jurisdictions increase incentives for participation in existing illicit tobacco markets. In the United States, the illicit tobacco market consists mostly of bootlegging from low-tax states to high-tax states and is less affected by large-scale smuggling or illegal production as in other countries. In the future, nonprice regulation of cigarettes - such as product design, formulation, and packaging - could in principle, contribute to the development of new types of illicit tobacco markets. Understanding the U.S.Illicit Tobacco Market reviews the nature of illicit tobacco markets, evidence for policy effects, and variations among different countries with a focus on implications for the United States. This report estimates the portion of the total U.S. tobacco market represented by illicit sales has grown in recent years and is now between 8.5 percent and 21 percent. This represents between 1.24 to 2.91 billion packs of cigarettes annually and between 2.95 billion and 6.92 billion in lost gross state and local tax revenues. Understanding the U.S. Illicit Tobacco Market describes the complex system associated with illicit tobacco use by exploring some of the key features of that market - the cigarette supply chain, illicit procurement schemes, the major actors in the illicit trade, and the characteristics of users of illicit tobacco.This report draws on domestic and international experiences with the illicit tobacco trade to identify a range of possible policy and enforcement interventions by the U.S. federal government and/or states and localities."--Publisher's description